Pemberdayaan Masyarakat Melalui PKBM untuk Meningkatkan Keterampilan Masyarakat Miskin - Aceng Ibrahim; Bachrun Rifa’i; Ratna Dewi (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2020)
This research reviews the efforts, program and impact of community learning center (PKBM) Raharja in improving the skills of the poor. The method used in this research was descriptive qualitative. The study of using data from the database, used to calculate data from databases, data, data, information and data from the data contained in information related to data, as well as information about data that has been analyzed. The results of the study of the expulsion of menstrual program, including training, training, counseling, diagnosis, program planning, and evaluation, as well as training programs for students who have passed the program. In the program Later, it is important to learn how to use the information provided by the Early Childhood Education (PAUD), which is part of the session of equality, which has been involved in the field of training, specializing in learning, development, communicating, teaching and teaching and learning. Community members present in the program, If you have any questions, please contact us anytime.